The SWOT analysis: marketing and promotional strategies used at the University of Malaya Library - Hazidah, N.A.; Edzan, N.N. (2012)
A library is the place to find knowledge that accommodates various information sources. Nevertheless, the promotion of the library is an important task that should be carried out by a library to improve its image, role and credibility. A library offers various collections, services and facilities to the users. Since an academic library plays an important role in the university, marketing and promotional strategies are crucial. This paper seeks to discuss the strategies used in marketing and promoting the University of Malaya Library (UML) effectively. The SWOT Analysis is used to generate strategies and actions. Identification of SWOTs is essential because subsequent steps in the process of planning for achieving the selected objective may be derived from SWOTs. In order to keep up with globalization, UML has embraced new technology such as Web 2.0 and SMS (Short Messaging System) alerts. Social media, such as Facebook, Twitter and other social networks are applications that the current generation uses for interaction. With the existence of resources, facilities and services that exceed users’ expectations, it will show that the library has promote the services effectively. Strategies and action plans designed to meet users’ needs could indirectly enhance and strengthen the image of the library as an information centre that can compete with other information resources such as bookstores and electronic media. Thus, promotion and marketing of the library should take precedence and there is a need for libraries to enhance their organization inline with users’ need.